Connectivity in Service Systems: Does Technology-Enablement Impact the Ability of a Service System to Co-Create Value?. (August 2013) - Breidbach, Christoph F.; Kolb, Darl G.; Srinivasan, Ananth
Does technology-enablement impact the ability of a service system to co-create value? In this study, we assess and compare the relative importance of Information and Communication Technology (ICT) and human relationships in service systems, by drawing on findings from a multiple case study in the consulting industry and subsequent analysis through a sociotechnical connectivity lens. We present a theoretical model and propositions which indicate that successful technology-enabled value co-creation is contingent upon the quantity and quality of interpersonal relationships, or social connectivity, between humans that interact and exchange resources by means of ICT. Our findings indicate that technology-enablement in service systems does not, in and of itself, influence human behavior, goals, or motivation regarding the value co-creation process, and argue that the ability of these service systems to co-create value is contingent on the levels of social connectivity between its human entities, more so than ICTs that enable the process. The ability to manage social connectivity therefore represents a prerequisite for the successful co-creation of value in technology-enabled environments, and we provide guidelines that help managing social connectivity on requisite levels.